Analysis of Judge’s Considerations in Rejection of Sharia Economic Dispute Decision Number 462/Pdt.G/2024/PA.Gs at Gresik Religious Court - haniatul fauziyah; Muttaqin Choiri Choiri (Program Studi Hukum Ekonomi Syari'ah, 2025)
Sharia economic dispute in Indonesia have become a crucial in the implementation of Islamic law in the economic sector. Religious Courts play a vital role in upholding justice in accordance with sharia principles, including in the resolution of sharia economic disputes. However, not all claims are admissible in court, as reflected in decision Number 462/Pdt.G/2024/PA.Gs at the Gresik Religious Cour, which rejected a sharia economic dispute lawsuit. This study aims to identify the reasons behind the judge’s rejection, describe the court’s decision in handling the dispute, and analyze the legal considerations used in the case. The research method used is qualitative library research with a normative juridical approach, focusing on the judge’s reasoning for rejecting the claim. Data collection techniques included documentation and interviews, while data analysis in this study employed a deductive approach. The findings reveal that: (1) The claim in case Number 462/Pdt.G/2024/PA.Gs was rejected due to insufficient valid evidence, such as dokuments or witness testimonies to support the plaintiff’s claim, rendering it inadmissible to the Religious Court. (2) The judge’s considerations emphasized the importance of clear and valid evidence in judicial proceedings, where the absence of sufficient proof led to the case being dismissed.